Сучасний стан проблеми боротьби з варроатозом бджіл - Санін, Ю. К. (Energy and Automation, 2017)
Current state of VARROATOSIS treatment of honybeesY. Sanin  Topicality. Varroatoz - invasive parasitic disease of bees, the varroa mite caused destructor. Varroatoz has substantial economic losses to beekeeping worldwide. In Europe, the loss of bee colonies indicated invasive disease ranged from 1.8 to 53% in North America - 30%, in Japan - 25% [1].The development of market relations and Ukraine's accession to the World Trade Organization involving the use of advanced manufacturers bee products electrotechnologies resource saving and means of implementation that would ensure a more qualitative, environmental and competitive products beekeeping by reducing its cost and productivity of bee colonies.One way of solving this problem may be the introduction of advanced, non-medicamentous more effective means of combating invasive and infectious diseases, in particular varroa destructor mites to prevent or reduce non-technical losses biopotential bee colonies and apiaries increase profitability.Analysis of recent research and publications. Analysis of existing trends combating varroatozom both in Ukraine and abroad. The object of research is the process of improving the efficiency of production processes and environmentally friendly production in beekeeping. The subject of the study is a set of theoretical, methodological and practical aspects of combating varroatozom. The study used common methods of abstraction, generalization, systematic approach to the phenomena studied, non-medicamentous ways and means and methods of mathematical statistics. In particular theoretical justification for fighting varroatozom used in beekeeping abstract logical method.A systematic analysis of theoretical and experimental studies of ways and means to destroy pathogenic organisms and fauna in beekeeping shows that none of diseases of bees is not written so many and diverse, as varroatoz. Study on the use of chemical, biological and physical means and methods of combating varroatozom.Results and discussion. For many years the problem of combating varroatozom although it has become less acute, but not completely solved. Although in recent years offered a fairly large number of tools and methods (both new and known modified) used for the prevention and treatment varroatozu, in practice, did not provide any apiary complete recovery. In addition, analysis of the scientific literature because of the uncontrolled use of potent chemicals against the varroa mite activated other diseases. It is established that the use akaretsydiv promotes the emergence and spread of askosferoza, foul brood and some viral infections [4]. AI Murawski and VM Miller noted that the use of chemical substances by dusting, spraying, prokapuvannya the streets with food or feeding pollutes the entire space of bee nests. This leads to accumulation residues of drugs in combs, feed stocks, hit them in the feed chain, linking adult bees and brood, which vyhodovuyetsya. Remains of drugs disrupt the conversion of larvae to adults, causing the appearance of immature bees with short life period, in addition, reduced immunity to all individuals bee family. During this treatment the bees in the struggle for survival, the whole brood autumn brought a loss of feed consumption. It is often amazed brood fungal, bacterial and viral infections by lowering the threshold of its stability. For example, as a result of research, it was found that the two-year use of chemicals aforementioned methods bee family weaken, their productivity is reduced by 20-80%, while the three-year treatment - bee family not survive until spring.Recently, domestic and foreign manufacturers bee products prefer to use the acaricidal plants and natural means of combating varroatozom. Based on the analysis of theoretical studies of biological means and ways to combat varroatozom and comparative critical analysis of their strengths and weaknesses can be considered that the existing approaches to the treatment of such diseases as varroatoz not fully meet the requirements for the preservation and expansion of biopotentials bee family, Veterinary both the requirements and on labor costs to ensure improvements in recovery bee colonies.The analysis of theoretical and experimental studies of physical ways and means to combat varroatozom indicate that the latter are under development and are aimed at the development and introduction of advanced research in science and technology practical bee farms. However, the literature on technologies using electromagnetic radiation in the optical range in the short-range to combat pathogenic microflora and fauna are no data regarding design, geometric dimensions and exhibits technological tools that enable you to more effectively combat varroatozom contactless non-medicamentous ways .Conclusions. 1. System analysis of scientific literature domestic and foreign authors whose works are devoted to finding a solution to the problem of combating the varroa mite, shows that this is a problem of global proportions that causes devastating impact on the beekeeping (reducing its productivity by 20-80%) and the crop (crop inefficient pollination entomophile) reduces their productivity by 20-30%.2. It is established that the existing methods and tools to combat this disease (chemical, biological, physical) do not fully meet the qualitative and quantitative indicators, to preserve and increase both the biopotential bee colonies Veterinary requirements and on labor costs for prevention and rehabilitation of bee colonies .3. A systematic analysis of the literature revealed no generalized theory influence physical means to combat varroatozom and the lack of a comprehensive approach to create suchasnyhelektrotehnolohiy for use in beekeeping lighting installations with improved energy and biophysical properties at the shortwave sources of ultraviolet light (UV).